Vertical transmission of hepatitis C virus: A tale of multiple outcomes - Escobar-Gutierrez, Alejandro; Soudeyns, Hugo; Larouche, Ariane; Carlos Carpio-Pedroza, Juan; Martinez-Guarneros, Armando; Vazquez-Chacon, Carlos A.; Fonseca-Coronado, Salvador; Yamasaki, Lilian H. T. [UNESP]; Ruiz-Tovar, Karina; Cruz-Rivera, Mayra (Elsevier B.V., 2013)
Globally, hepatitis C virus (HCV) infection affects approximately 130 million people and 3 million new infections occur annually. HCV is also recognized as an important cause of chronic liver disease in children. The absence of proofreading properties of the HCV RNA polymerase leads to a highly error prone replication process, allowing HCV to escape host immune response. The adaptive nature of HCV evolution dictates the outcome of the disease in many ways. Here, we investigated the molecular evolution of HCV in three unrelated children who acquired chronic HCV infection as a result of mother-to-child transmission, two of whom were also coinfected with HIV-1. The persistence of discrete HCV variants and their population structure were assessed using median joining network and Bayesian approaches. While patterns of viral evolution clearly differed between subjects, immune system dysfunction related to HIV coinfection or persistent HCV seronegativity stand as potential mechanisms to explain the lack of molecular evolution observed in these three cases. In contrast, treatment of HCV infection with PegIFN, which did not lead to sustained virologic responses in all 3 cases, was not associated with commensurate variations in the complexity of the variant spectrum. Finally, the differences in the degree of divergence suggest that the mode of transmission of the virus was not the main factor driving viral evolution. (C) 2013 Elsevier B. V. All rights reserved.
Keywords: Hepatitis C virus; Vertical transmission; Molecular evolution